AN ALUMINUM SILOXIDE COMPLEX FOR STEREOSELECTIVE POLYMERIZATION OF RACEMIC LACTIDE - Yu Zhang; Xuan Pang; Lili Ma; Zhaohui Tang (Journal of the Chilean Chemical Society, 2017)
Stereoselective polymerization of lactide is receiving growing attention in polymer science. Herein, a five-coordinate aluminum siloxide complex, [2,2-dimethyl- 1,3-propylenebis(3,5-di-tert- butylsalicylideneiminato)] (triphenyl-silanolato) aluminium (III) (1), was prepared from AlEt3, N,N´-(2,2-dimethylpropylene) bis(3,5-di-tert-butylsalicylideneimine) and triphenyl-silanol. X-ray analysis demonstrated that 1 contained a five-coordinate aluminum atom with distorted trigonal bipyramidal geometry in the solid state. 1H NMR and 13C NMR spectra indicated that the two conformational stereoisomers of 1 tautomerizes rapidly in chloroform or toluene solution at room temperature. 1 showed high stereoselectivity (Pm = 0.84) for the ROP of rac-lactide in toluene at 100°C, and polymerized rac-lactide to crystalline polymer (Tm = 178°C). This is the first report of stereoselective polymerization of rac-lactide using aluminum siloxide as a catalyst.